2013
DOI: 10.1126/science.1236083
|View full text |Cite
|
Sign up to set email alerts
|

Organization of the Mitotic Chromosome

Abstract: Mitotic chromosomes are among the most recognizable structures in the cell, yet for over a century their internal organization remains largely unsolved. We applied chromosome conformation capture methods, 5C and Hi-C, across the cell cycle and revealed two alternative three-dimensional folding states of the human genome. We show that the highly compartmentalized and cell-type-specific organization described previously for non-synchronous cells is restricted to interphase. In metaphase, we identify a homogenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

141
1,061
5
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 940 publications
(1,231 citation statements)
references
References 49 publications
141
1,061
5
7
Order By: Relevance
“…2e) or with up- and down-regulated transcription (Extended Data Figure 5c). This major reorganization of chromatin architecture is also reflected in the curves of contact frequency P(s) as a function of genomic distance s 3,29 . In control samples, like in other mammalian cells 14,15 , P(s) curve has two regimes: a more shallow decay for s<200Kb ( P(s)~s −0.7 ), and a steeper scaling for 200Kb < s < 3Mb ( P(s)~s −1.2 ).…”
Section: Disappearance Of Tads and Peaksmentioning
confidence: 93%
“…2e) or with up- and down-regulated transcription (Extended Data Figure 5c). This major reorganization of chromatin architecture is also reflected in the curves of contact frequency P(s) as a function of genomic distance s 3,29 . In control samples, like in other mammalian cells 14,15 , P(s) curve has two regimes: a more shallow decay for s<200Kb ( P(s)~s −0.7 ), and a steeper scaling for 200Kb < s < 3Mb ( P(s)~s −1.2 ).…”
Section: Disappearance Of Tads and Peaksmentioning
confidence: 93%
“…However, the initiation and progression of replication, followed by the segregation of the sister chromatids (SCs) into daughter cells, is expected to modify the genome higher‐order organization. Recent studies have unveiled cell‐cycle stage‐specific genome‐wide topological variations in bacteria, yeast, fly, and mammals (Naumova et al , 2013; Guidi et al , 2015; Marbouty et al , 2015; Hug et al , 2017). As expected, in all species the largest reorganization transition is associated with SC condensation, a fundamental process occurring concomitantly to their individualization, and facilitating their proper segregation.…”
Section: Introductionmentioning
confidence: 99%
“…While Hi‐C studies on mammalian and drosophila cells have confirmed this compaction change and provided important insights on the organization of mitotic chromosomes’ internal structure (Naumova et al , 2013; Hug et al , 2017), no comprehensive analysis of the 4D dynamics of the chromosomes during an entire eukaryotic cell cycle has been achieved. To explore new chromosomal structural features over the cell cycle progression, we analyzed the internal folding and overall organization of S. cerevisiae genome over 15 synchronized time points and the role of cohesin and condensin using Hi‐C (Dekker et al , 2002; Lieberman‐Aiden et al , 2009).…”
Section: Introductionmentioning
confidence: 99%
“…During mitosis, the chromosomes markedly condense, RNA polymerase is excluded from the chromatin, and transcription ceases. Recent chromosome conformation capture studies show that the three-dimensional partitioning of genomic domains in interphase is almost completely lost during mitosis (Naumova et al 2013). During mitotic exit, such domains are re-established, RNA polymerase re-engages the chromatin, and the entire genome becomes transcriptionally activated in a manner that faithfully recapitulates the prereplicated state of the cell (Egli et al 2008).…”
Section: Pioneer Factors As Bookmarking Factors In Mitosismentioning
confidence: 99%